Studi Potensi Subak Tanah Yeng Sebagai Kawasan Agrowisata di Desa Sedang, Kecamatan Abiansemal, Kabupaten Badung - YANTI, NI KOMANG DHARMA; LILA, KOMANG ARTHAWA; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Tanah Yeng Subak Potential Study as an Agrotourism in Sedang Village, Abiansemal, Badung Regency Subak as a world heritage needs to be preserved. The issue of existence reduction of subak cause decreasing of Bali tourism attractiveness that really gives huge impact to Balinese economic-social life. One of the alternatives to prevent agricultural land into non-agricultural land is developing subak becomes agro-tourism object. Tanah Yeng Subak is one of subak that is located in Desa Sedang, Abiansemal, Badung Regency which has a big potency to be developed as an agro-tourism object. The aim of this writing is to identify the tourism potencies of Subak Tanah Yeng which can be developed become a tourism activities object. The result of the research that have been collected shows some tourism potencies of Subak Tanah Yeng, such as: the accessibility to this area is easy to reach, friendly population, regular planting rotation, cultivating diversity commodities, good maintained Subak Temple, 89,2% of the population are in productive ages, local instances that support economic matters of the population, strong and unique customs in terms of farming ceremony and Subak Tanah Yeng also provides beautiful landscape.